COVID‐19 in a child with primary antibody deficiency. Issue 2 (8th December 2020) - Ahanchian, Hamid; Moazzen, Nasrin; Sezavar, Majid; Khalighi, Negar; Khoshkhui, Maryam; Aelami, Mohammad Hassan; Motevalli Haghi, Nasrin Sadat; Rezaei, Nima
Abstract: Although presentation of COVID‐19 in patients with immunodeficiency could be mild, it should not be missed, while early diagnosis and appropriate treatment can survive infected patients. Because even severe infections in PID patients may be presented with few symptoms and signs, this diagnosis should be considered in those immunocompromised patients who have exacerbating preexisting symptoms. Abstract : Although presentation of COVID‐19 in patients with immunodeficiency could be mild, it should not be missed, while early diagnosis and appropriate treatment can survive infected patients. Because even severe infections in PID patients may be presented with few symptoms and signs, this diagnosis should be considered in those immunocompromised patients who have exacerbating preexisting symptoms.